Interaction of cardiac implantable electronic device and patent foramen ovale in ischemic stroke: A case‐only study. Issue 3 (31st January 2019) - Agboola, Kolade M.; Lee, Jin‐Moo; Liu, Xiaoyan; Novak, Eric; Cuculich, Phillip S.; Cooper, Daniel H.; Noheria, Amit
Abstract: Background: Cardiovascular implantable electronic device (CIED) leads are a nidus for right atrial thrombi. Right‐to‐left thromboembolism across a patent foramen ovale (PFO) is a putative mechanism for ischemic stroke and PFO has been associated with stroke. We used a novel unbiased case‐only study design to assess the effect modification of PFO‐associated ischemic stroke risk by presence of CIED. We hypothesized that presence of CIED, as a nidus for right atrial thrombus formation, magnifies the PFO‐ischemic stroke relationship; therefore, among hospitalized ischemic stroke patients we would find a higher prevalence of CIED in patients with PFO. Methods: We included consecutive first ischemic stroke patients admitted to our hospital from 2006 to 2015, who were enrolled in a prospectively maintained stroke registry. PFO was ascertained from documentation on echocardiography, and presence of CIED at time of stroke was determined from chest radiography reports at or prior to hospitalization. We measured distributions of CIED within PFO and control groups and used Fisher's exact test to evaluate the PFO‐CIED association among ischemic stroke patients. Results: We included 7089 patients (age: 64.5 ± 14.9 years, 51% female). Echocardiography diagnosed PFO in 760 (10.7%) patients and CIED was reported on chest radiography in 752 (10.6%) patients. Prevalence of CIED was lower in the PFO (61/760, 8.0%) compared to control group (691/6329, 10.9%), P = 0.015. Conclusion: Among admitted ischemic stroke patients, we did not find a higher prevalence of CIED in patients with PFO compared to controls. Therefore, in the underlying source population, the presence of CIED did not increase the PFO‐associated ischemic stroke risk.